ANALISIS STRATEGI PENGEMBANGAN USAHATANI LADA HITAM DI DESA KARET JAYA KECAMATAN BUAY PEMACA KABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2021)
Researching, Analysis of the development strategy of black pepper farming (Piper Ningrum Linn) in Karet Jaya Village, Buay Pemaca District, South Ogan Komering Ulu District. This study aims to determine internal factors (strengths and weaknesses) and external factors (opportunities and threats) and the development of black pepper farming (Piper ningrum Linn) and analyze the strategy of developing black pepper farming in Karet Jaya Village, Buay Pemaca District, South Ogan Komering Ulu. Location determination was deliberately carried out by Perposive with the consideration that in Karet Jaya Village was one of the black pepper producers in Karet Jaya Village, Buay Pemaca District, South Ogan Komering Ulu District.The method used in this study is the survey method and sampling method used in this study is an unbalanced randomized method that uses 23 black pepper farmers, 6 traders, 3 consumers and 1 agricultural instructor, the types of data used are primary and secondary data. Data processing is done by using SWOT Analysis to find out internal factors and what external factors are related to the development of black pepper farming and to analyze the development strategy of black pepper farming in Karet Jaya Village, Buay Pemaca District, South Ogan Komring Ulu District. Based on this research, it is known that the internal factors of developing black pepper farming are strength (have a large enough land, access to market farmers is good enough, farmers have experience in pepper farming). And with weaknesses (Limited working capital, processing of less hygienic pepper, farmers as price takers). As well as external factors in developing black pepper farming is an opportunity (Demand for pepper is increasing, availability of labor). And with threats (the emergence of new competitors in pepper farming, jaundice, the price of pepper decreases). And the strategy for developing black pepper farming is SO strategy (Increasing land area, intensifying pepper farming, can maximize production costs), ST strategy (Improving production quality, Using experience to overcome pest and disease control methods), WO strategy (Government should provide capital assistance , making a more hygienic place in pepper processing. WT Strategy (Partnership with traders / Suppliers). Keyword : Researching, Analysis, development strategy